PENDAMPINGAN PENERAPAN MEDIA GAME EDUKATIF BERKELOMPOK WORD SEARCH GAME UNTUK MENINGKATKAN MINAT BELAJAR BAHASA ARAB SISWA MTS AL-HILAAL BANDA - Nor Holis bin Nafsah; Immatul Khoiroh; Fahrija Djufri Rahim (INAIFAS Press, 2026)
Arabic at MTs Al-Hilaal Banda is often perceived as difficult, resulting in low student interest. This is influenced by monotonous teaching methods, limited media variation, and low student engagement. To address this issue, this study applies a group-based educational game, namely a word search game, to enhance students’ interest in learning Arabic. The game is designed to make students more enthusiastic and active in recognizing and memorizing vocabulary through enjoyable activities. This study focuses on the implementation process and the results of applying the game to eighth-grade students’ learning interest. The objective is to describe the implementation and identify its impact on improving learning interest. This research uses a qualitative descriptive-interpretative approach, with data from teachers and students, supported by documents and field notes. Data were collected through observation, interviews, and documentation, then analyzed through reduction, display, and conclusion drawing. The results show increased interest, participation, and vocabulary mastery.